Analisis Persediaan Bahan Baku Kacang Koro Pedang (Canavalia ensiformis) Pada UD Arjuna Bali, Desa Nyanglan, Kecamatan Banjarangkan, Kabupaten Klungkung - SUMBERDAN, I WAYAN OKI; SUAMBA, I KETUT; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.5, Desember 2015, 2016)
A bstrack Inventory Analysis of Raw Materials Jack Beans (Canavalia ensiformis) On UD Arjuna Bali , Nyanglan Village, District Banjarangkan , Klungkung . UD Arjuna Bali raw material needs from 2011 till 2014 has increased , so it is necessary to analyze raw material inventory in anticipation of delays in arrival of raw materials that may occur and minimize the total inventory costs incurred by company . The purpose of study was to determine the efficiency of raw material inventory costs UD Arjuna Bali by comparing the total cost of the actual inventory cost and the total cost of inventory using the inventory control of raw materials effectively. Results of the study include ordering raw materials costs that should be done in company by booking of 6.601,48 kg , with a frequency of four times in one period . safety stock should be owned companies amounted to 196,66 kg . Reorder point made when inventory in warehouse of 393,32 kg and inventories amounted to 6.798,14 kg is maximum inventor . Cost efficiencies gained Rp 232.557,69 or 4, 76 % based on the difference between total cost of a real inventory of Rp 4.880.000,00 to the total cost of inventory after the analysis of Rp 4.647.442,31. The company expected to adopt the analysis efficiency of raw material inventory more efficiently and can be allocated for other purposes . Keywords : Jack Beans , Economical Order Quantity and cost efficiency